2009
DOI: 10.1038/emboj.2009.7
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for competitive interactions of Pex14 with the import receptors Pex5 and Pex19

Abstract: Protein import into peroxisomes depends on a complex and dynamic network of protein-protein interactions. Pex14 is a central component of the peroxisomal import machinery and binds the soluble receptors Pex5 and Pex19, which have important function in the assembly of peroxisome matrix and membrane, respectively. We show that the N-terminal domain of Pex14, Pex14(N), adopts a three-helical fold. Pex5 and Pex19 ligand helices bind competitively to the same surface in Pex14(N) albeit with opposite directionality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 33 publications
9
103
0
3
Order By: Relevance
“…A recent biophysical study showed that the presence of multiple WXXX(F/Y) motifs in the N terminus of Pex5 allows the formation of higher order complexes with the Pex14-NTD in vitro, although it is not clear whether this also reflects the situation in peroxisomes in vivo (14,15). Interestingly, human Pex19, which is supposed to act as an import receptor/chaperone for peroxisomal membrane proteins, binds competitively to the same surface in Pex14-NTD via an amphipathic helix-forming pentapeptide sequence (16). In contrast to typical Pex5 WXXX(F/Y) motifs, the identified FFXXXF of Pex19 binds with opposite directionality.…”
Section: In Human Cells This Interaction Is Mediated By Seven Consermentioning
confidence: 99%
See 4 more Smart Citations
“…A recent biophysical study showed that the presence of multiple WXXX(F/Y) motifs in the N terminus of Pex5 allows the formation of higher order complexes with the Pex14-NTD in vitro, although it is not clear whether this also reflects the situation in peroxisomes in vivo (14,15). Interestingly, human Pex19, which is supposed to act as an import receptor/chaperone for peroxisomal membrane proteins, binds competitively to the same surface in Pex14-NTD via an amphipathic helix-forming pentapeptide sequence (16). In contrast to typical Pex5 WXXX(F/Y) motifs, the identified FFXXXF of Pex19 binds with opposite directionality.…”
Section: In Human Cells This Interaction Is Mediated By Seven Consermentioning
confidence: 99%
“…Pex14-(16 -80) and Pex5-(1-110) for NMR studies were expressed as fusion proteins with a His 6 tag followed by a tobacco etch virus cleavage site as described previously for Pex14-(16 -80) (16). 13 affinity chromatography followed by tobacco etch virus cleavage and removal of the His 6 tag by a second Ni 2ϩ affinity chromatography step.…”
Section: Construction Of Pex5 Fragment Expression Vectors-formentioning
confidence: 99%
See 3 more Smart Citations